Integrating Cartographic Knowledge Within a Geoportal: Interactions and Feedback in the User Interface - Panchaud, Nadia H.; Hurni, Lorenz (Cartographic Perspectives, 2018)
<!-- p.p1 {margin: 0.0px 0.0px 12.0px 24.0px; text-align: justify; line-height: 14.0px; font: 11.0px 'Adobe Caslon Pro'} --> Custom user maps (also called map mashups) made on geoportals by novice users often lead to poor cartographic results, because cartographic expertise is not part of the mapmaking process. In order to integrate cartographic design functionality within a geoportal, we explored several strategies and design choices. These strategies aimed at integrating explanations about cartographic rules and functions within the mapmaking process. They are defined and implemented based on a review of human-centered design, usability best practices, and previous work on cartographic applications. Cartographic rules and functions were made part of a cartographic wizard, which was evaluated with the help of a usability study. The study results show that the overall user experience with the cartographic functions and the wizard workflow was positive, although implementing functionalities for a diverse target audience proved challenging. Additionally, the results show that offering different ways to access information is welcomed and that explanations pertaining directly to the specific user-generated map are both helpful and preferred. Finally, the results provide guidelines for user interaction design for cartographic functionality on geoportals and other online mapping platforms.